2008
DOI: 10.1038/mp.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in inflammation-related genes are associated with susceptibility to major depression and antidepressant response

Abstract: There are clinical parallels between the nature and course of depressive symptoms in major depressive disorder (MDD) and those of inflammatory disorders. However, the characterization of a possible immune system dysregulation in MDD has been challenging. Emerging data support the role of T-cell dysfunction. Here we report the association of MDD and antidepressant response to genes important in the modulation of the hypothalamic-pituitaryadrenal axis and immune functions in Mexican Americans with major depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
147
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(157 citation statements)
references
References 59 publications
7
147
2
1
Order By: Relevance
“…In this issue of Molecular Psychiatry, Segman et al We recently reported increased expression of the 10-kDa interferongamma-induced protein CXCL10 in depressed patients; CXCL10 levels decreased back to normal after antidepressant treatment. 2 On the basis of our genetic findings of association with T bet (TBX21) as well as the functional finding of increased CXCL10 activity, we proposed increased Th1 immune activity in depression. Of interest here, most of Segman's findings were of decreased gene expression in postpartum depression, while we reported increased levels of CXCL10.…”
mentioning
confidence: 99%
“…In this issue of Molecular Psychiatry, Segman et al We recently reported increased expression of the 10-kDa interferongamma-induced protein CXCL10 in depressed patients; CXCL10 levels decreased back to normal after antidepressant treatment. 2 On the basis of our genetic findings of association with T bet (TBX21) as well as the functional finding of increased CXCL10 activity, we proposed increased Th1 immune activity in depression. Of interest here, most of Segman's findings were of decreased gene expression in postpartum depression, while we reported increased levels of CXCL10.…”
mentioning
confidence: 99%
“…MLB has also been demonstrated to inhibit lipopolysaccharide-induced expression of inflammatory molecules (Zhao et al, 2013). Inhibition of neuroinflammation may represent a novel mechanism of action for antidepressant treatment (Wong et al, 2008). Several recent studies have reported that some natural products such as omega-3 fatty acids and curcumin induced antidepressant effects through the modulation of oxidative reactions and inflammatory cytokine production in the brain (Lin et al, 2011;Su, 2009;Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rs4792888 showed marginal evidence of association with desipramine response [160]. Other investigations showed a possible involvement of rs2270007 [158] and rs2267716-rs255105 [159] within CRHR2 in citalopram response, and of rs917195 in desipramine efficacy [161].…”
Section: Crh Receptors (Crhr1 and Crhr2)mentioning
confidence: 99%